Poly-S-Nitrosated Albumin as a Safe and Effective Multifunctional Antitumor Agent: Characterization, Biochemistry and Possible Future Therapeutic Applications. (30th December 2013) - Ishima, Yu; Kragh-Hansen, Ulrich; Maruyama, Toru; Otagiri, Masaki
Abstract : Nitric oxide (NO) is a ubiquitous molecule involved in multiple cellular functions. Inappropriate production of NO may lead to disease states. To date, pharmacologically active compounds that release NO within the body, such as organic nitrates, have been used as therapeutic agents, but their efficacy is significantly limited by unwanted side effects. Therefore, novel NO donors with better pharmacological and pharmacokinetic properties are highly desirable. The S -nitrosothiol fraction in plasma is largely composed of endogenous S -nitrosated human serum albumin (Mono-SNO-HSA), and that is why we are testing whether this albumin form can be therapeutically useful. Recently, we developed SNO-HSA analogs such as SNO-HSA with many conjugated SNO groups (Poly-SNO-HSA) which were prepared using chemical modification. Unexpectedly, we found striking inverse effects between Poly-SNO-HSA and Mono-SNO-HSA. Despite the fact that Mono-SNO-HSA inhibits apoptosis, Poly-SNO-HSA possesses very strong proapoptotic effects against tumor cells. Furthermore, Poly-SNO-HSA can reduce or perhaps completely eliminate the multidrug resistance often developed by cancer cells. In this review, we forward the possibility that Poly-SNO-HSA can be used as a safe and effective multifunctional antitumor agent.